2017
DOI: 10.1002/cmdc.201600597
|View full text |Cite
|
Sign up to set email alerts
|

Form Matters: Stable Helical Foldamers Preferentially Target Human Monocytes and Granulocytes

Abstract: Some hybrid foldamers of various length, all containing the (4R,5S)-4-carboxy-5-methyloxazolidin-2-one (d-Oxd) moiety alternating with an l-amino acid (l-Val, l-Lys, or l-Ala), were prepared in order to study their preferred conformations and to evaluate their biological activity. Surprisingly, only the longer oligomers containing l-Ala fold into well-established helices, whereas all the other oligomers give partially unfolded turn structures. Nevertheless, they all show good biocompatibility, with no detrimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This material was used as a control instead of synthetic/geogenic CaCO 3 since (i) it had exactly the same elemental composition, (ii) the same particle size distribution is not obtainable with synthetic/geogenic CaCO 3 , and (iii) it has been reported that the synthetic/geogenic CaCO 3 has higher chemical stability and lower porosity than the biogenic one. , It was also decided not to use oyster powder as a control after the heat treatment that removes the organic matrix, as this process generates additional porosity . Subsequently, the coupling reaction of Rho-B piperazine (Figure , detailed procedure in SI) with oyster shell particles was set up following an optimized experimental procedure. , Our idea was to form a peptide bond between the free amine group of the Rho-B piperazine (using piperazine as a linker) and the exposed carboxyl groups of the protein, mostly due to the presence of glutamic and aspartic acid moieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This material was used as a control instead of synthetic/geogenic CaCO 3 since (i) it had exactly the same elemental composition, (ii) the same particle size distribution is not obtainable with synthetic/geogenic CaCO 3 , and (iii) it has been reported that the synthetic/geogenic CaCO 3 has higher chemical stability and lower porosity than the biogenic one. , It was also decided not to use oyster powder as a control after the heat treatment that removes the organic matrix, as this process generates additional porosity . Subsequently, the coupling reaction of Rho-B piperazine (Figure , detailed procedure in SI) with oyster shell particles was set up following an optimized experimental procedure. , Our idea was to form a peptide bond between the free amine group of the Rho-B piperazine (using piperazine as a linker) and the exposed carboxyl groups of the protein, mostly due to the presence of glutamic and aspartic acid moieties.…”
Section: Resultsmentioning
confidence: 99%
“…25 Subsequently, the coupling reaction of Rho-B piperazine (Figure 2, detailed procedure in SI) with oyster shell particles was set up following an optimized experimental procedure. 26,27 Our idea was to form a peptide bond between the free amine group of the Rho-B piperazine (using piperazine as a linker) and the exposed carboxyl groups of the protein, mostly due to the presence of glutamic and aspartic acid moieties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%